A Computer-Based Approach to Teaching Foreign Languages - Shaturaev, Jakhongir; Khamitovna, Khakimova Khulkar (ASEAN Journal of Educational Research and Technology, 2023)
In the context of the modernization of modern education, practical teachers strive for independence in the choice of teaching aids, in particular, foreign languages (FL), for a creative rethinking of the content of education and increasingly resort to the use of modern methods and information technologies in the learning process. The processes of global informatization of all spheres of public life are developing in the world community. The level of information technology development and its pace depends on the state of the economy, the quality of life of people, national security, and the role of the state in the world community. In all developed countries and many developing countries, there are intensive processes of informatization of education.